1973
DOI: 10.1364/ao.12.002509
|View full text |Cite
|
Sign up to set email alerts
|

Microscope with Enhanced Depth of Field and 3–D Capability

Abstract: In the summer of 1969, R. L. Gregory was working at Bell Labs, and suggested one might be able to increase the effective depth of field of a microscope if, instead of making the objective achromatic, one arranged that the different spectral colors come to foci at different distances from the lens. J. S. Courtney-Pratt suggested that one might then be able to view the image in 3-D by use of a simple binocular eyepiece modified to give a convergence of the images that varied with the spectral color. A 16-mm NA 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This chromatic aberration also is undesirable, and designs are normally geared toward its elimination (Downs 1981, Torok andHarvey 1984). However, it has been shown that the chromatic aberration effects can be used to enhance the depth of field of an optical microscope (Courtney-Pratt 1973. 1976) and has been made the basis of a noncontact optical probe, spectroscope, and profilometer (Molesini 1984.…”
Section: Aberrations In Optical Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This chromatic aberration also is undesirable, and designs are normally geared toward its elimination (Downs 1981, Torok andHarvey 1984). However, it has been shown that the chromatic aberration effects can be used to enhance the depth of field of an optical microscope (Courtney-Pratt 1973. 1976) and has been made the basis of a noncontact optical probe, spectroscope, and profilometer (Molesini 1984.…”
Section: Aberrations In Optical Systemsmentioning
confidence: 99%
“…A surface profiling technique utilizing chromatic aberration of the microscope objective has been shown to be practical (Courtney-Pratt 1976, Courtney-Pratt andGregory 1973) and can be extended to the confocal scanning microscopy method of surface profiling. It has been suggested that the chromatic aberration of the microscope objective in the CSLM can be exploited (Kino and Corle 1989) and Boyde (1987) has made use of the depth resolution of confocal optics in producing colour-coded stereo images on the TSRLM.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Previous bifocal microscopes have either modified the objective by the insertion of a birefringent element or they used objectives that were designed for large chromatic aberration, 8 so that images are formed in different polarizations or wavelengths. 6,7 Previous bifocal microscopes have either modified the objective by the insertion of a birefringent element or they used objectives that were designed for large chromatic aberration, 8 so that images are formed in different polarizations or wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…The distortion introduced by light microscope systems has been studied by several authors; more recently the analysis has been extended to optical serial sectioning systems. Early work in optical serial sectioning and related techniques was considered by Burke et al (1971), Hausler (1972) and Courtney-Pratt & Gregory (1973). Stoksetch (1969) gave an expression for the twodimensional microscope transfer function subsequently used in iterative algorithms for reconstructing serial section images (Agard, 1984;Castleman, 1979).…”
Section: Introductionmentioning
confidence: 99%